The Determinants Of Credit Ratings: U.S. Capital Goods Firms - TEH, CHUCK OOI (2020)
Purpose – The objective of this paper is to elucidate the research question of which factors are important in determining the credit ratings of U.S. firms in the Capital Goods industry. Specifically, this study examines the financial risk and business risk variables that could influence a firm’s credit rating.